Mifepristone enhances the neural efficiency of human visuospatial memory encoding and recall. (March 2021) - Yalin, Nefize; Kempton, Matthew J.; Mazibuko, Ndaba; Mehta, Mitul A.; Young, Allan H.; Stokes, Paul RA
Abstract: Glucocorticoid receptor (GR) antagonism is a promising new treatment for cognitive dysfunction in psychiatric disorders but the effects of GR antagonism on cognition related brain activity is poorly understood. This study examines the effects of the GR and progesterone receptor antagonist mifepristone on the neural correlates of visuospatial learning and working memory in healthy male participants. The study used a pharmacological functional magnetic resonance imaging (fMRI) design to determine mifepristone effects on visuospatial paired associates learning (vPAL) and n-back working memory (WM) fMRI task related brain activations. 20 right-handed healthy male participants received 600 mg mifepristone or placebo on two separate imaging days and each participant performed fMRI tasks four hours later. The effect of mifepristone on task related brain activations was determined using Region of Interest (ROI) fMRI analyses and an exploratory whole brain voxel-wise fMRI task analyses was also conducted. The vPAL task ROI analysis found that mifepristone administration was significantly associated with decreased fusiform cortex activations in first and second encoding blocks (p = 0.007, p = 0.04) and decreased angular and precuneal cortices activations in the first recall block (p = 0.01, p = 0.02). There were no significant differences in fMRI brain activations associated with mifepristone administration in the n-back task ROI's (all p > 0.05). Mifepristone administration did not significantly affect fMRI brain activations in the whole brain voxel-wise analyses for both tasks. N-back and vPAL task reaction times and accuracy were similar in both mifepristone and placebo conditions (all p > 0.05). Our finding of decreased fusiform, angular and precuneal vPAL task related brain activity associated with mifepristone administration for the same behavioural performance as found in the placebo condition may represent improved efficiency of visuospatial memory encoding and recall. These findings provide evidence that mifepristone may enhance the efficiency of human visuospatial memory and calls for further studies in patient populations using an fMRI approach to provide proof of concept for new treatments. Highlights: First study to investigate the effects of mifepristone on cognitive brain activations. Mifepristone decreased activations in fusiform cortex in vPAL encoding. Mifepristone decreased activations in angular and precuneal cortices in vPAL recall. Mifepristone may enhance efficiency of visuospatial memory encoding and recall.